A REPORT ON INCIDENCE OF CANDIDIASIS IN NATIVE CHICKENS - A. Balasubramaniam; T.V. Tamilam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Incidence of candidiasis and its ability to be a primary infection in a native chicken flock of 500 birds reared in cage system was reported. Grossly, pseudomembranous growth giving turkey-towel appearance was noticed in dead birds. Crops from affected chicken yielded Candida albicans was confirmed by culture and germ tube production in poultry serum from the crop samples collected from affected birds. Administration of copper sulphate was found to be effective in containing illness and the signs associated with candidiasis in the affected flock.